Biological preliminary studies on Halticus pygmaeus (Hemiptera: Miridae) : II. Host preference on leguminous forage crops - Carrizo, P. (Agrociencia Uruguay, 1999)
Preference studies on Halticus pygmeus, on laboratory conditions and on plots were carried out. In laboratory studies, species offered were: Trifolium repens, T. pratense (two varieties), Medicago sativa and M. lupulina. By mean of a choice assay, was tested preference in Petri boxes. The most attacked specie was lucerne, followed by white clover (Tuckey,α =0,05). Total surface offered had no influence on attack. On plots, the species were: white clover, red clover, and a grasses mix. Most collections were made on white clover, whose caught showed a significative positive correlation (Pearson, α=0,05) with total sweepnet caught.